Tools for a resilient agriculture in the Caribbean - Tirtopawiro, Laurenzo (Inter-American Institute for Cooperation on Agriculture (IICA), 2023)
Mr. Laurenzo Tirtopawiro, Agricultural Technology and Innovation Specialist, Inter-American Institute for Cooperation on Agriculture (IICA) - Suriname, Mr. Kent Coipel, Technical Specialist, Inter-American Institute for Cooperation on Agriculture (IICA) - Dominica, Mr. Craig Thomas, National Specialist, Inter-American Institute for Cooperation on Agriculture (IICA) - Antigua & Barbuda